2006
DOI: 10.1007/s10620-006-3077-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Treated by Gastroplasty

Abstract: Nonalcoholic steatohepatitis (NASH), which is the most severe histologic form of nonalcoholic fatty liver disease (NAFLD), is emerging as the most common clinically important form of liver disease in obese patients. The prevalence of NASH may increase with the rise in the rate of obesity and metabolic syndrome in affluent communities. The aim of this work is to describe clinical and histopathologic findings and correlate liver tissue damage to the length of duration of the obesity in the group of patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 22 publications
2
32
0
3
Order By: Relevance
“…Jaskiewicz et al 145 conducted a study on 10 individuals who underwent a wedge biopsy during gastroplasty and had a new repeat biopsy eight months later. They observed significant improvements of the degenerative and inflammatory hepatic lesions in the repeat biopsies and liver function readings, eight months after the surgery.…”
Section: Gastric Banding and Banded Gastroplastymentioning
confidence: 99%
“…Jaskiewicz et al 145 conducted a study on 10 individuals who underwent a wedge biopsy during gastroplasty and had a new repeat biopsy eight months later. They observed significant improvements of the degenerative and inflammatory hepatic lesions in the repeat biopsies and liver function readings, eight months after the surgery.…”
Section: Gastric Banding and Banded Gastroplastymentioning
confidence: 99%
“…There are, however, some concerns about the effects of rapid weight loss, which was reported to enhance portal inflammation and fibrosis (Andersen et al, 1991). Results from follow-up studies were not conclusive about the risk of disease progression after bariatric surgery (Kral et al, 2004;Jaskiewicz et al, 2006;De Ridder et al, 2007;Furuya et al, 2007).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…10 However, Results from different studies show that the prevalence of NAFLD varies between 16.7% and 96% in morbidly obese patients subjected to bariatric surgery. [10][11][12][13][14][15][16][17][18][19][20][21][22] The wide range of NAFLD prevalence depends on the biochemical criteria and the method sensitivity used to detect NAFLD. 8,23 Furthermore, NASH, as a progressive manifestation of NAFLD, occurs in 7.3% to 98% of such patients.…”
Section: Prevalence Of Nafld and Nash In Bariatric Candidatesmentioning
confidence: 99%
“…8,23 Furthermore, NASH, as a progressive manifestation of NAFLD, occurs in 7.3% to 98% of such patients. 10,12,13,17,18,[20][21][22][24][25][26][27][28][29][30] The study which reported NASH in 98% of their patients, indicated that the mean super obese state (Mean BMI 52.8 kg ⁄m 2 ) in their population is the reason of high NASH prevalence. 30 Another study concluded that the differences in NASH prevalence can be explained by the histological criteria used to diagnose NASH.…”
Section: Prevalence Of Nafld and Nash In Bariatric Candidatesmentioning
confidence: 99%
See 1 more Smart Citation